Artificial Intelligence: Current Challenges and Future Perspectives - Al-Ameri, Laith Thamer; Hameed, Ekhlas Khalid (AL-Kindy College Medical Journal, 2023)
Artificial intelligence is a discipline of computer science that gives machines the intelligence resembles that of humans and empowers them to acquire knowledge, evaluate, and handle issues when exposed to information in different formats. AI is now useful as a powerful tool to help researchers collect, deal with, and analyze large sets of data in a fast and cost-effective way; additionally, a statistical collection and analysis of a vast amount of dataset of enormous numbers of published research articles will be with a high level of accuracy. However, Artificial intelligence has many struggles, conflicts, and challenges that need to be discussed and clarified.